Matter-element model and its application to land resource eco-security assessment - ZHANG Hong-bo; LIU Li-ming; ZHANG Jun-lian; ZHU Zhan-qiang (浙江大学学报. 农业与生命科学版)
Focusing on the characteristics of regional land resource eco-security and main eco-problems of land ecosystem in loess hilly area, an index system was established based on pressure-state-response framework and analytic hierarchy process (AHP). And an integrated assessment model was constructed with the support of matter-element model and extension engineering theory. The assessment model was applied to Pengyang county, a typical loess hilly area, located in northwest of China. The results indicate that condition of land eco-security of study area showed improved trend from 1986 to 2004, while it still means to be under a critical security level nowadays; Overall results obtained by such model are basically consistent with the local condition, which illustrates that the integrated assessment model is reliable and feasible, and can be used as a new method to evaluate land eco-security. However, as a developing math tool, the matter-element model also has some flaws, such as few correlation functions available etc., so further research and analysis should be done to improve its application to the land eco-security assessment and ongoing refinement and constructive feedback are sought from practitioners.